In-Office, Multisinus Balloon Dilation: 1-Year Outcomes from a Prospective, Multicenter, Open Label Trial. Issue 2 (March 2014) - Gould, James; Alexander, Ian; Tomkin, Edward; Brodner, David
Background: The objective of this prospective, multicenter study was to assess 1-year changes in sinonasal symptoms and health care use after office-based multisinus balloon dilation. Methods: Adults diagnosed with chronic or recurrent acute rhinosinusitis per the 2007 adult sinusitis guidelines were en d in this Institutional Review Board-approved study. Balloon dilation of the maxillary sinuses/ethmoid infundibula with or without frontal or sphenoid ostial dilation was performed in the physician's office under local anesthesia. Intraoperative procedure technical success and subject procedure tolerance were recorded. Efficacy was assessed using the patient-reported 20-item Sino-Nasal Outcome Test (SNOT-20) and Rhinosinusitis Symptom Inventory (RSI). Complications and revision surgeries were also recorded. Results: A total of 313 ostial dilations were attempted and 307 were successfully completed (98.1%) in 81 subjects. Mean procedure tolerance was 2.8 ± 2.2 (0 = no pain; 10 = severe pain). Clinically meaningful and statistically significant (p < 0.0001) mean SNOT-20 symptom improvement was observed at 1 and 6 months and sustained through 1 year. The RSI treatment effect for all major rhinosinusitis symptoms was "large" and improvement in each was significant (p < 0.0001). Compared with the previous 1-year period, patients reported an average of 2.3 fewer acute sinus infections (p < 0.0001), 2.4 fewer antibiotic courses taken (p < 0.0001), and 3.0 fewer sinus-related physician visits (p < 0.0 1) after balloon dilation. No serious device or procedure-related adverse events occurred. One subject (1.3%) underwent revision surgery. Conclusion: In-office, multisinus balloon dilation is safe, effective, and well tolerated. Patients reported significant reductions in both sinonasal symptoms and health care use after balloon dilation. Efficacy observed at 1 and 6 month follow-up was sustained through 1 year with a very low rate of revision surgery. This study was a part of the clinical trial NCT01612780 registered atwww.clinicaltrials.gov